JARIMAH KHALWAT ARRANGEMENTS IN QANUN NUMBER 6 OF 2014 CONCERNING JINAYAT AND ITS POLYMICS IN ACEH - Bukhari Bukhari; Asmuni Asmuni; Muhammad Hatta; Anwar Anwar (istinbath, 2022)
This study aims to determine the punishment for various polemics regarding jinayat khalwat in the province of Aceh, especially in the cities of Banda Aceh, Lhoksukon and Langsa. This study uses a normative-empirical method with a statutory approach and a case approach. The data source in this research is the Al-Qur`an; the 1945 Constitution; Law No. 1 of 1946 concerning the Criminal Code; Law No. 8 of 1981 concerning the Criminal Procedure Code; Aceh Qanun No. 6 of 2014 concerning Jinayat Law; and Aceh Qanun No. 7 of 2013 concerning Jinayat Procedural Law. The results of the study show that the background to the regulation on the prohibition of khalwat crimes in Qanun No. 6 of 2014 concerning the Law of Jinayat is to prevent the occurrence of a larger jinayat, namely adultery, both adultery muhsan and ghairu muhsan. The formation of the nomenclature of jinayat khalwat in this Qanun is a form of concern for the Government of Aceh towards “decency” regulations relating to actions that lead to jinayat of adultery. The community fully supports the formation of jinayat khalwat rules that aim for the good and benefit of the ummah even though there is polymic in this finger khalwat arrangement.